PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN SEKOLAH DASAR NEGERI PONTIANAK KOTA - Nasrullah, Nasrullah; Sabri, Tahmid; Rosnita, Rosnita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the effect of the use of audio visual media on the learning outcomes of the fourth grade citizenship education in Pontianak City Elementary School 03 City. The method used is an experiment with the form of Quasi-Experimental Design design and non equivalent control group design. The population is all students from three classes totaling 93 people, the sample of this study is IVC grade students totaling 31 people as a control class and IVA class students as an experimental class totaling 32 people. Data collection techniques used are measurement techniques, data collection tools are multiple choice written tests. The results of the data obtained the average results of the post-test experimental class class 77.69 and the average post-test control 73.03. Hypothesis test results using t-test (Polled Variance) obtained t count = 2.403 while for dk (32 + 31-2 = 61) with a significant level Î± = 5% obtained t table = 0.643, which means thitung> t table, then Ha is accepted, this prove there is an influence of audio visual media in learning Civic Education. Based on the results of the effect size (ES) calculation, ES = 0.43 is included in the medium criteria.Â Keywords: Influence, Media, Audio-Visual, Civic Education, Learning Outcomes